POLA USAHATANI KOMODITAS TANAMAN PANGAN PADA LAHAN KERING DI KABUPATEN MOROWALI PROVINSI SULAWESI TENGAH - Noer, Hasmari (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
The study was conducted to determine the pattern of crop farming cultivation on dry land, that the cropping pattern and crop rotation on crop farming in CentralSulawesi province Morowali. The method used is a survey method. The research location in Central Sulawesi province Morowali. The sampling technique used random sampling. The research sample amounted to 76 respondents are spread across three districts namely North Bungku District, District and Sub Mori Petasia Top Morowali Central Sulawesi province. Data collection through interviews using questionnaires and literature. The results of the analysis of the utilization patterns of farming will be described descriptively. The results of this research, two cropping patterns by farmers. I was cropping farmers cropping pattern similar, namely rice paddy, corn-corn-soybean and soy nuts. Cropping Patterns II farmers cropping upland rice-Crops (corn) and upland rice-or soy. Farmers in implementing crop rotation patterns adjust to the conditions and rainfall in accordance with the experience and knowledge of farmers onclimate conditions